Political versus economic institutions in the growth process - Emmanuel Flachaire; Cecilia García-Peénalosa; Maty Konte (Center for Economic Studies and ifo Institute (CESifo), 2011)
After a decade of research on the relationship between institutions and growth, scholars in this field seem to be divided. Economic institutions perform well in growth regressions and a body of literature argues that this supports the key importance of institutions for development. Other authors maintain that the type of constraints that the recent theoretical literature describes are the more stable political institutions, and these have been found to play no role in empirical growth analyses. In this paper we re-examine the role that institutions play in the growth process using cross-section and panel data for both developed and developing economies over the period 1970-2000. Our results indicate that the data is best described by an econometric model with two growth regimes. Political institutions are the key determinant of which growth regime an economy belongs to, while economic institutions have a direct impact on growth rates within each regime. These findings support the hierarchy of institutions hypothesis, whereby political institutions set the stage in which economic institutions and policies operate.
Keywords: O43; O47; 330; growth; institutions; cross-country regressions; mixture regressions; Wirtschaftswachstum; Institutionalismus; Schätzung; Welt